Clinical predictors of long-term outcome in obsessive-compulsive disorder - Jakubovski, Ewgeni (Depression and anxiety, 2013)
Background The purpose of this study was to investigate demographic and clinical factors associated with the long-term outcome of obsessive-compulsive disorder (OCD). Methods A hundred ninety-six previously untreated patients with DSM-IV criteria OCD completed a 12-week randomized open trial of group cognitive-behavioral therapy (GCBT) or fluoxetine, followed by 21 months of individualized, uncontrolled treatment, according to international guidelines for OCD treatment. OCD severity was assessed using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) at different times over the follow-up period. Demographics and several clinical variables were assessed at baseline. Results Fifty percent of subjects improved at least 35% from baseline, and 21.3% responded fully (final Y-BOCS score < or = 8). Worse prognosis was associated with earlier age at onset of OCD (P = 0.045), longer duration of illness (P = 0.001) presence of at least one comorbid psychiatric disorder (P = 0.001), comorbidity with a mood disorder (P = 0.002), higher baseline Beck-Depression scores (P = 0.011), positive family history of tics (P = 0.008), and positive family history of anxiety disorders (P = 0.008). Type of initial treatment was not associated with long-term outcome. After correction for multiple testing, the presence of at least one comorbid disorder, the presence of a depressive disorder, and duration of OCD remained significant. Conclusions Patients under cognitive-behavioral or pharmacological treatment improved continuously in the long run, regardless of initial treatment modality or degree of early response, suggesting that OCD patients benefit from continuous treatment. Psychiatric comorbidity, especially depressive disorders, may impair the long-term outcome of OCD patients.
Published online 25 October 2012
Gesehen am 09.07.2018